2022
DOI: 10.1021/acs.accounts.2c00256
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acids as a Playground for the Computational Study of the Photophysics and Photochemistry of Multichromophore Assemblies

Abstract: Metrics & MoreArticle Recommendations CONSPECTUS:The interaction between light and multichromophoric assemblies (MCAs) is the primary event of many fundamental processes, from photosynthesis to organic photovoltaics, and it triggers dynamical processes that share remarkable similarities at the molecular scale: light absorption, energy and charge transfer, internal conversions, emission, and so on. Those events often involve many chromophores and different excited electronic states that are coupled on an ultraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 69 publications
2
53
1
Order By: Relevance
“…The measurement of an absorption or electronic circular dichroism (ECD) spectrum is one of the first and most basic steps to identify and characterize the static and dynamical behavior of a DNA sequence. Indeed, the formation of a DNA duplex is mirrored by typical changes in the UV absorption spectrum relative to the isolated nucleobases, typically manifested as a relatively large hypochromic effect. ,, At the same time, the different possible duplex conformations, that is, B-DNA, A-DNA, and Z-DNA, are characterized by well-defined ECD signatures. , Unfortunately, the UV light absorption by DNA has also potentially harmful consequences, since it can trigger a cascade of photophysical and photochemical processes that can lead to apoptosis or to the damage of the genetic code and, therefore, to carcinogenesis. , The study of the interaction between DNA and UV light is thus important from several perspectives, from the (bio)­analytical to the (bio)­medical one, explaining the huge number of experimental and theoretical studies devoted to characterize the photophysics of oligo- and polynucleotides. Independently of the particular aspect of the UV/DNA interaction one is interested in, a proper inclusion of conformational effects is surely important. Despite the overall stability, at room temperature, DNA (and RNA) are fluctuating multichromophore assemblies (MCAs), , which can exhibit significant deviations from the “average” structure, with consequent different interactions with UV light.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of an absorption or electronic circular dichroism (ECD) spectrum is one of the first and most basic steps to identify and characterize the static and dynamical behavior of a DNA sequence. Indeed, the formation of a DNA duplex is mirrored by typical changes in the UV absorption spectrum relative to the isolated nucleobases, typically manifested as a relatively large hypochromic effect. ,, At the same time, the different possible duplex conformations, that is, B-DNA, A-DNA, and Z-DNA, are characterized by well-defined ECD signatures. , Unfortunately, the UV light absorption by DNA has also potentially harmful consequences, since it can trigger a cascade of photophysical and photochemical processes that can lead to apoptosis or to the damage of the genetic code and, therefore, to carcinogenesis. , The study of the interaction between DNA and UV light is thus important from several perspectives, from the (bio)­analytical to the (bio)­medical one, explaining the huge number of experimental and theoretical studies devoted to characterize the photophysics of oligo- and polynucleotides. Independently of the particular aspect of the UV/DNA interaction one is interested in, a proper inclusion of conformational effects is surely important. Despite the overall stability, at room temperature, DNA (and RNA) are fluctuating multichromophore assemblies (MCAs), , which can exhibit significant deviations from the “average” structure, with consequent different interactions with UV light.…”
Section: Introductionmentioning
confidence: 99%
“…We have applied our method to thymine, a prototypical heteroatomic ring, whose photophysical behavior is the focus of ongoing experimental and computational studies. ,, The vRR spectra computed in the gas phase are in good agreement with the experimental ones, measured in water, for what concerns both the position and the relative intensity of the different peaks. The only significant discrepancy between the two sets of data concerns the high energy region (>1600 cm –1 ), where three peaks are present in the computed spectra, to be compared with the single experimental peak.…”
Section: Discussionmentioning
confidence: 81%
“…Previous photochemical studies on a very wide range of modestly modified natural nucleobases have revealed their unique nature in terms of their highly efficient excited-state decay pathways. [49][50][51][52] Mimicking and synthetically controlling these photodynamics has proven extremely challenging. 9,15 The loss of the OH group at the C3 position has implications for the design of synthetic nucleobases, as this group is directly involved in the hydrogen-bonding motif of the base pair.…”
Section: Pccp Papermentioning
confidence: 99%